Workplace triggers that can lead to burnout syndrome in secondary school teachers - Herrera-Herrera, Karen (2025)
Aim. The general purpose of the research was to analyze the triggering factors in the work context that can generate greater vulnerability to suffering from Burnout Syndrome in a sample of science teachers. Methodology. According to the nature of the work, it was located within the naturalistic paradigm, responding to the dominant mixed, qualitative approach. Questionnaires and interviews were applied to 14 science teachers, and a class observation was carried out in five institutions. The analysis was carried out descriptively, contrasting qualitative and quantitative elements. The validity process occurred through triangulation. Results. When analyzing the findings, it was found that the main trigger of the work context of Burnout Syndrome in the people participating in the research is work overload and situations associated with the sociocultural context in which the educational center is located. The triggering aspects associated with the sociocultural context that generated the greatest impact were situations of violence, the low social appreciation of the profession, and the lack of support from fathers, mothers, and guardians towards the teaching staff. Regarding the triggering situations associated with work overload, the following were determined: attention to SEN and the execution of administrative tasks. Recommendations. It is recommended to strengthen teacher training in the recognition, prevention, and management of Burnout Syndrome; reorganize the administrative burden to avoid work overload; and propose institutional strategic plans.